2000
DOI: 10.1038/sj.jea.7500116
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for assessing children's organophosphorus pesticide exposures in agricultural communities

Abstract: Children can be exposed to pesticides from multiple sources and through multiple pathways. In addition to the standard pathways of diet, drinking water and residential pesticide use, children in agricultural communities can be exposed to pesticides used in agricultural production. A research program on children and pesticides was established at the University of Washington ( UW ) in 1991 and has focused on two major exposure pathway issues: residential proximity to pesticide -treated farmland and transfer of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 9 publications
3
56
0
Order By: Relevance
“…A recent longitudinal study of the urinary OP metabolite levels of children living in an area where OP pesticides are used in agriculture found that the metabolite concentrations were higher in months when OPs were used on orchards, despite no direct contact of family members with the pesticides or location near the sprayed orchards (Koch et al, 2002). In a study of CPF levels in house dust compared to urinary TCP levels for children of pesticide applicators, farm workers, and nonagricultural workers, urinary TCP did not match well the parental occupation, although it did match home garden pesticide use (Fenske et al, 2000(Fenske et al, , 2002b. Observed levels of TCP may not match well the potential intake of CPF in nonacute exposure settings.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A recent longitudinal study of the urinary OP metabolite levels of children living in an area where OP pesticides are used in agriculture found that the metabolite concentrations were higher in months when OPs were used on orchards, despite no direct contact of family members with the pesticides or location near the sprayed orchards (Koch et al, 2002). In a study of CPF levels in house dust compared to urinary TCP levels for children of pesticide applicators, farm workers, and nonagricultural workers, urinary TCP did not match well the parental occupation, although it did match home garden pesticide use (Fenske et al, 2000(Fenske et al, , 2002b. Observed levels of TCP may not match well the potential intake of CPF in nonacute exposure settings.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…The first type of model included factors for sampling location (day care vs. home) and POP concentrations. The POP data in play area soil were not included in the model, because these concentrations in soil were low, and initial analyses as well as literature reports (Fenske et al, 2000) showed that soil was not a significant factor for the urinary metabolite concentrations. The second type of model included factors for sampling location and estimated aggregate daily POP doses.…”
Section: Statistical Assessmentsmentioning
confidence: 99%
“…Although recent research efforts have collected much needed data to improve our understanding of the potential exposures of young children in their homes, child care centers, and other environments (Zartarian et al, 1995(Zartarian et al, , 1997(Zartarian et al, , 1998Bradman et al, 1997Bradman et al, , 2007Byrne et al, 1998;Gurunathan et al, 1998;Landrigan et al, 1999;Adgate et al, 2000Adgate et al, , 2001Fenske et al, 2000bFenske et al, , 2002Freeman et al, 2001;Lu et al, 2001;MacIntosh et al, 2001;Pang et al, 2002;Clayton et al, 2003;Curl et al, 2003;Duggan et al, 2003;Shalat et al, 2003;Wilson et al, 2003Wilson et al, , 2004Hore et al, 2005;Morgan et al, 2005;Perera et al, 2006), it is not clear what factors most influence a child's potential exposure to pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, urinary dialkylphosphate (DAP) metabolites of OP pesticides have been quantified in human urine as a dosimeter for exposure and bodily adsorption of OP pesticides (Bradway and Shafik, 1977;Reid and Watts, 1981;Bardarov and Mitewa, 1989;Fenske and Leffingwell, 1989;Weisskopf and Seiber, 1989;Drevenkar et al, 1991;Aprea et al, 1994Aprea et al, , 1996aAprea et al, , b, 1999Aprea et al, , 2000Davies and Peterson, 1997;Loewenherz et al, 1997;Moate et al, 1999;Simcox et al, 1999. Fenske et al, 2000Hardt and Angerer, 2000;Heudorf and Angerer, 2001;Lu et al, 2001;Oglobline et al, 2001a, b;Bravo et al, 2002;CDC, 2002;Cocker et al, 2002;Garfitt et al, 2002a, b).…”
Section: Introductionmentioning
confidence: 99%